A novel rodent model of severe renal ischemia reperfusion injury. (25th November 2016) - Whalen, Henry; Shiels, Paul; Littlejohn, Marc; Clancy, Marc
Abstract: Renal ischemia reperfusion injury (IRI) is a major problem, currently without treatments in clinical use. This reflects the failure of animal models to mimic the severity of IRI observed in clinical practice. Most described models lack both the ability to inflict a permanent reduction in renal function and the sensitivity to demonstrate the protective efficacy of different therapies in vivo. To test novel cell-based therapies, we have developed a model of renal IRI in Fisher 344 rats. Animals were subjected to 120 min of unilateral warm ischemia, during which they underwent an intra-renal artery infusion of therapeutic agents or vehicle. At either 2 or 6 weeks post-surgery, animals underwent terminal glomerular filtration rate (GFR) studies by inulin clearance to most accurately quantify renal function. Harvested kidneys underwent histological analysis. Compared to sham operations, saline treated animals suffered a long-term reduction in GFR of ≈50%. Histology revealed short- and long-term disruption of renal architecture. Despite the injury severity, post-operative animal losses are <5%. This model produces a severe, consistent renal injury that closely replicates the pathological processes encountered in clinical medicine. Renal artery infusion mimics the route likely employed in clinical transplantation, where the renal artery is accessible. Inulin clearance characterizes GFR, allowing full assessment of therapeutic intervention. This model is useful for screening therapeutic agents prior to testing in a transplant model. This reduces animal numbers needed to test drugs for clinical transplantation and allows for refinement of dosing schedules.